University Faculty of the 21st Century: Challenges from Costa Rican Higher Education - Paniagua-Cortés, Yarina (2021)
The hiring profile for professors that has been widely accepted for years in higher education institutions does not guarantee that these professionals develop all the skills required to fulfill the needs the world has today. In most cases, this profile includes being an expert in their area, having relevant professional experience, and doing research to produce knowledge and new advances. However, this is no longer sufficient, considering how complex and constantly changing our world is. That is why this essay discusses other qualities that are essential to any higher education professor in our current society. Pedagogical expertise, emotional competence, differentiation, knowledge of technological tools and their implications, being part of academic networks, mobility, foreign language proficiency, professional development and reflection are essential in order to fulfill both society's and students' needs so that professors' work is pertinent now and as preparation for the future.